The role of CYP-sEH derived lipid mediators in regulating mitochondrial biology and cellular senescence: implications for the aging heart - Yousef, Ala; Fang, Liye; Heidari, Mobina; Kranrod, Joshua; Seubert, John M. (Frontiers in Pharmacology, 2024)
Cellular senescence is a condition characterized by stable, irreversible cell cycle arrest linked to the aging process. The accumulation of senescent cells in the cardiac muscle can contribute to various cardiovascular diseases (CVD). Telomere shortening, epigenetic modifications, DNA damage, mitochondrial dysfunction, and oxidative stress are known contributors to the onset of cellular senescence in the heart. The link between mitochondrial processes and cellular senescence contributed to the age-related decline in cardiac function. These include changes in mitochondrial functions and behaviours that arise from various factors, including impaired dynamics, dysregulated biogenesis, mitophagy, mitochondrial DNA (mtDNA), reduced respiratory capacity, and mitochondrial structural changes. Thus, regulation of mitochondrial biology has a role in cellular senescence and cardiac function in aging hearts. Targeting senescent cells may provide a novel therapeutic approach for treating and preventing CVD associated with aging. CYP epoxygenases metabolize N-3 and N-6 polyunsaturated fatty acids (PUFA) into epoxylipids that are readily hydrolyzed to diol products by soluble epoxide hydrolase (sEH). Increasing epoxylipids levels or inhibition of sEH has demonstrated protective effects in the aging heart. Evidence suggests they may play a role in cellular senescence by regulating mitochondria, thus reducing adverse effects of aging in the heart. In this review, we discuss how mitochondria induce cellular senescence and how epoxylipids affect the senescence process in the aged heart.